Research Trends in Technology-Enhanced Language Learning: A Bibliometric Analysis - Nasution, Awal Kurnia Putra; Batubara, Muhammad Hasyimsyah (Asosiasi Dosen Perguruan Tinggi Islam, 2024)
Using bibliometric methods allows a quantitative understanding of the growth of TELL, and analysis of topic trends provides insight into the evolution of research interests, including significant growth in topics such as